UJI RESISTENSI BAKTERI Escherichia coli DARI SUMBER AIR BAKU DI KARAWANG TERHADAP ANTIBIOTIK SIPROFLOKSASIN - Diniarti, Fuji Ayu; Kasasiah, Ahsanal; Hilmi, Indah Laily (APDFI (Asosiasi Pendidikan Diploma Farmasi Indonesia), 2022)
Infectious diseases are included in the ten most common diseases in Indonesia. The disease can be overcome by the use of antimicrobials, one of which is antibiotics. Antibiotics are drugs used to treat infections caused by bacteria. Excessive use of antibiotics without clear indications can have an impact on the occurrence of bacterial resistance to these antibiotics. One of the bacteria that is resistant to antibiotics is Escherichia coli. This study aims to determine the sensitivity of Escherichia coli isolated from raw water sources in Karawang to the antibiotic ciprofloxacin. Samples were obtained from irrigation water which is the source of raw water for one branch of Perumdam in Karawang. The samples were tested using Lactose Broth (LB) media, then confirmed using Eosin Methylene Blue (EMBA) media to confirm the presence of Escherichia coli bacteria equipped with Gram stain. Bacterial resistance test was carried out using Mueller Hinton Agar (MHA) media with disc diffusion method. The results showed that the average diameter of the clear zone formed around the paper disc was 30.16 mm. The isolates showed intermediate results against the antibiotic ciprofloxacin.